Analysis of a Grounding System In 20 Kv Distribution Transformer Line in PLTD Gayo Lues - Israq Israq; Muhammad Muhammad; Andik Bintoro; Biswas Babu Pokhrel (International Journal of Advances in Data and Information Systems, 2022)
The main purpose of grounding is to create a low-impedance path to the earth's surface for electric waves and transient voltages. An effective grounding system will minimize these effects. The grounding system plays a very important role in the protection system. The grounding system is used as a fault current discharge path to the ground. According to its function, grounding is divided into 2, namely grounding the neutral point of the power system and grounding equipment. The neutral grounding of the power system serves as a safety system or network, while the grounding of the equipment functions as a safety against touch voltage. Measurement of the type of grounding electrode on a 20 kV distribution transformer at PT. PLN Rema Gayo Lues Area uses 2 rod electrodes with a grounding resistance value of 2 Ohms.